(untitled) (Bangladesh Journal of Urology, 2020)
Introduction: Urinary retention can be either chronic or acute in onset. Urinary retention can result from impaired detrusor contractility or obstruction of bladder outlet. Twenty five to 30% of men with decreased flow are not obstructed 1. Either uroflowmetry or post-void residue (PVR) can not differentiate obstruction from impaired detrusor contractility. In this study, an effort has been paid to know the usefulness of pressure-flow study in urinary retention due to suspected benign prostatic hyperplasia(BPH) cases for predicting the outcome of surgery. Methods: This is a before after clinical study, conducted in Bangabandhu Sheikh Mujib Medical University, Dhaka. Total 32 patients were selected for the study. Patients age ranges from 49-78 years.Patients with chronic and refractory urinary retention due to BPH were enrolled for the study. They were divided into group A (pre-operative) and group B (Post-operative). TURP was done in all 32 patients by single surgeon. Study variables were detrusor pressure at maximum flow (Pdet@Qmax), bladder outlet obstruction index(BOOI), bladder contractility index( BCI) and post void residue (PVR). Result: Total number of patients was 32. Age ranges from 49-78 years. Twenty one (65.6%) had BPH with chronic retention and 11 (34.4%) had BPH with refractory retention.Pdet@Qmax between Group A and Group B was highly significant (p=0.001). But difference is not significant in Pdet@Qmax d” 40 subgroup of patients (p=0.673). Bladder outlet obstruction index between Group A and Group B is highly significantly (p=0.001), but, that does not observed in BOOI <20 subgroup(p=0.600). Bladder contractility index in both Normal (BCI 100-150) and strong ( BCI >150 ) subgroups are significant ( p=0.001 and 0.001 respectively ). But it is not significant in BCI<100 sub group (p=0.021). Post void residue between Group A and Group B is highly significant (p=0.001). But in PVR >300m subgroup, difference is insignificant (p=0.120). Conclusion: In this study, overall favorable outcome observed in all patients after TURP but Pdet@Qmax <40 cm of water, BOOI <20, BCI <100 and PVR >300 ml groups of patients are at high risk of unfavorable clinical outcome after TURP. With the help of presence flow study (PFS) prior knowledge of these factors, it is possible to predict postoperative outcome. Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.74-77